Strategi Kepemimpinan Partisipatif Dalam Meningkatkan Kinerja Pegawai di Kantor Camat Amandraya - Lusia Lenni Lestari Buulolo; Krisnawati Setyaningrum Nugraheni (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to analyze participative leadership strategies in improving employee performance at the Amandraya Sub-district Office, South Nias Regency. As the frontline of public service, leadership at the sub-district level plays a crucial role in mobilizing human resources in island regions. This study adopts a qualitative approach with a case study design. Data were collected through semi-structured interviews, participatory observation, and documentation studies involving the Sub-district Head and staff selected via purposive sampling. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña. The results indicate that participative leadership is implemented through five core strategies: democratic leadership style, involvement in decision-making, persuasive approaches in supervision, providing appreciation, and employee capacity development. These strategies have proven to enhance work effectiveness, organizational communication flow, and task responsiveness. These findings reinforce Social Exchange Theory, where leadership support is reciprocated with increased employee commitment. Despite operating within a hierarchical bureaucratic culture, the lean organizational structure of the sub-district allows participative strategies to function more effectively than at larger organizational levels.